Defining Bedaquiline Susceptibility, Resistance, Cross-Resistance and Associated Genetic Determinants: A Retrospective Cohort Study - Ismail, Nazir A. (EBioMedicine, 2018)
BACKGROUND: Bedaquiline (BDQ) is a novel agent approved for use in combination treatment of multi-drug resistant tuberculosis (MDR-TB). We sought to determine BDQ epidemiological cut-off values (ECVs), define and assess interpretive criteria against putative resistance associated variants (RAVs), microbiological outcomes and cross resistance with clofazimine (CFZ). METHODS: A retrospective cohort study was conducted. Minimal inhibitory concentrations (MIC) to BDQ were determined using 7H9 broth microdilution (BMD) and MGIT960. RAVs were genetically characterised using whole genome sequencing. BDQ ECVs were determined using ECOFFinder and compared with 6-month culture conversion status and CFZ MICs. FINDINGS: A total of 391 isolates were analysed. Susceptible and intermediate categories were determined to have MICs of ≤ 0.125 μg/ml and 0.25 μg/ml using BMD and ≤ 1 μg/ml and 2 μg/ml using MGIT960 respectively. Microbiological failures occurred among BDQ exposed patients with a non-susceptible BDQ MIC, an Rv0678 mutation and ≤ 2 active drug classes. The Rv0678 RAVs were not the dominant mechanism of CFZ resistance and cross resistance was limited to isolates with an Rv0678 mutation. INTERPRETATION: Criteria for BDQ susceptibility are defined and will facilitate improved early detection of resistance. Cross- resistance between BDQ and CFZ is an emerging concern but in this study was primarily among those with an Rv0678 mutation.